Indirect effects of an ecosystem engineer: how the Canadian beaver can drive the reproduction of saproxylic beetles. (18th September 2017) - Mourant, A.; Lecomte, N.; Moreau, G.
Abstract: Environmental rearrangements by ecosystem engineers influence food‐web characteristics by altering resource accessibility/availability in the newly created habitat. However, the paucity of empirical studies on this indirect interaction has hindered the integration of ecosystem engineering and food‐web theory. Here, we investigated the effect of the Canadian beaver Castor canadensis on the activity, realized fecundity and ecosystem functions provided by saproxylic beetles by quantifying beetle emergence holes on woody debris within the Kouchibouguac National Park, New Brunswick, Canada. We tested the hypothesis that perturbation induced by beaver activity enhances the activity and realized fecundity of saproxylic beetles by modifying their habitat and resource accessibility. We used 16 sites identified as beaver modified, each paired with a control site <500 m away. At each site, we quantified insect emergence holes on snags at increasing distances from the watercourse. Our results suggest that engineered habitat patches enhance the activity and reproduction of saproxylic beetle species, small emergence holes from Scolytinae being only observed in abundance on small trees located close to the watercourse and large emergence holes from Cerambycidae being one third more abundant throughout beaver‐modified sites. The complementary relationship between the Canadian beaver and saproxylic beetles demonstrates the potential for conservation measures encapsulating all of these organisms. Abstract : Environmental rearrangements by ecosystem engineers can influence food‐web characteristics by altering resource accessibility/availability in the newly created habitat. We tested the hypothesis that perturbation induced by beaver activity enhances the activity and realized fecundity of saproxylic beetles by modifying their habitat and resource accessibility, by quantifying insect emergence holes on snags around beaver‐engineered sites. Results suggest that engineered habitat patches enhance the activity and reproduction of saproxylic beetle species, demonstrating the complementary relationship between the Canadian beaver and saproxylic beetles and the potential for conservation measures encapsulating all of these organisms.